Single-shot soft x-ray laser linewidth measurement using a grating interferometer - Wang, Y., author; Yin, L., author; Wang, S., author; Marconi, M. C., author; Dunn, J., author; Gullikson, E., author; Rocca, J. J., author; Optical Society of America, publisher (Colorado State University. Libraries, 2013)
The linewidth of a 14.7 nm wavelength Ni-like Pd soft x-ray laser was measured in a single shot using a soft x-ray diffraction grating interferometer. The instrument uses the time delay introduced by the gratings across the beam to measure the temporal coherence. The spectral linewidth of the 4d1S0-4p1P1 Ni-like Pd lasing line was measured to be Δλ/λ=3×10-5 from the Fourier transform of the fringe visibility. This single shot linewidth measurement technique provides a rapid and accurate way to determine the temporal coherence of soft x-ray lasers that can contribute to the development of femtosecond plasma-based soft x-ray lasers.
Keywords: Fourier transforms; laser amplifiers; laser sources; soft x rays; x ray interferometry; x ray lasers